Boosting H2 Generation Coupled with Selective Oxidation of Methanol into Value‐Added Chemical over Cobalt Hydroxide@Hydroxysulfide Nanosheets Electrocatalysts - Xiang, Kun; Wu, Dan; Deng, Xiaohui; Li, Mei; Chen, Shanyong; Hao, Panpan; Guo, Xuefeng; Luo, Jing‐Li; Fu, Xian‐Zhu (Advanced functional materials, 2020)
The sluggish kinetics of oxygen evolution reaction (OER) is the main bottleneck for the electrocatalytic water splitting to produce hydrogen (H2), and the by‐product is worthless O2. Therefore, designing a thermodynamically favorable oxidation reaction to replace OER and coupling with value‐added product generation on the anode is of significance for boosting H2 generation under low electrolysis voltage. Herein, cobalt hydroxide@hydroxysulfide nanosheets on carbon paper (Co(OH)2@HOS/CP) are synthesized as bifunctional electrocatalysts to facilitate H2 production and convert methanol to valuable formate simultaneously. Benefiting from the influences/changes on the composition, surface properties, electronic structure, and chemistry of Co(OH)2, the as‐obtained electrodes exhibit very high selectivity for methanol to value‐added formate oxidation (MFO) and boost electrocatalytic performance with low overpotential of 155 mV for MFO and 148 mV for hydrogen evolution reaction at a current density of 10 mA cm−2. Furthermore, the integrated two‐electrode electrolyzer drives 10 mA cm−2 at a cell voltage of 1.497 V with united 100% Faradaic efficiency for anodic and cathodic reaction and continuous 20 h of operation without obvious decay. The electrocatalytic hydrogen production with the assistance of alternative oxidation by the robust electrocatalyst can be further used to realize the upgrading of other organic molecules with less energy consumption. New cobalt hydroxide@hydroxysulfide nanosheet electrocatalysts are developed to boost hydrogen fuel generation by coupling with selective oxidation of methanol to a value‐added formate. As a result, the electrolysis voltage is reduced to 1.497 V at a current density of 10 mA cm−2 and the Faradaic efficiencies are closed to 100% at the anode and cathode.